Saving the World One Block at a Time. (18th November 2019) - Lucas, Matt
Abstract: Blockchain is often associated with high energy usage, writes Matt Lucas from IBM's blockchain team. But, is the environmental impact of this much-hyped technology as bad as we've been led to believe?